What can be learned from the impact of the COVID-19 crisis on work participation among people with work disabilities? A qualitative practice & policy perspective approach - Mara de Visser; Trees Juurlink; Astrid Bosma; Marloes Zijl; Johannes R. Anema; Maaike A. Huysmans (BMC Public Health)
Abstract Background Previous studies among people with work disabilities (WD) showed that during the COVID-19 pandemic they were at risk for negative outcomes on work participation and health. These studies focused on people’s own accounts of their difficulties to work and did not include the policy and practice perspective. The aim of the present study was to explore the policy and practice perspective on what can be learned from the impact of the COVID-19 crisis, and what is needed to enhance work participation among people with WD, in times of crisis and beyond. Methods We used a multi-stakeholder perspective qualitative approach. Between March 2021 and September 2022, twenty-five semi-structured in-depth online interviews were conducted with occupational health professionals (13), employers (7) and policymakers (5). Participants were asked to share their experiences about employees or job seekers with work disabilities on (re)gaining and maintaining paid employment, barriers and facilitators for work participation during the Covid-19 crisis and what is needed to enhance work participation among people with WD in times of crisis and beyond. Data were analysed using thematic content analysis. Results The results indicated that, although employers rapidly implemented new working arrangements, people with WD had a vulnerable labour market position during the COVID-19 crisis, especially those with temporary contracts. Job loss and detrimental effects on mental health were identified. Other barriers to work participation included hampered collaboration between stakeholders during lockdowns and fewer job opportunities due to workplace shutdowns. Nevertheless, employers and occupational health professionals noticed that some employees were surprisingly flexible and capable with regard to performing alternative work tasks. We also identified ways to improve work participation for people with WD, including simplifying legislation and establishing sustainable policies on employment, investing in career development, creating an inclusive organizational culture and increasing accessibility to information and support assistance. Conclusions People with WD had a vulnerable labour market position during the COVID-19 crisis. The introduction of new working arrangements became widespread during the COVID-19 crisis, which had both positive and negative consequences for people with WD. Our results showed that improving work participation for people with WD requires a multifaceted approach, which can be achieved by the practical and policy recommendations offered by this study.